MICROCYCLONES FOR POLLEN SEPARATION FROM AIR STREAM: MICROCYCLONES FOR POLLEN SEPARATION FROM AIR STREAM - Živkov, Andreja (Journal on Processing and Energy in Agriculture, 2026)
The increasing concentration of airborne pollen presents significant challenges for public health and indoor air quality, resulting in development of efficient and compact separation technologies. This study focuses on the development and performance evaluation of microcyclones for the separation of pollen particles from air stream. Microcyclones utilize centrifugal forces generated by swirling airflow to separate particles based on their aerodynamic properties, offering advantages such as low maintenance, absence of filter media and continuous operation. The design methodology of the microcyclone is presented, including geometric parameters and air flow parameters selection to enhance pollen collection efficiency while minimizing pressure drop. In this study, a numerical simulation was performed to analyze the flow field prior to conducting the simulation of pollen particle separation from the air stream. The results indicated that properly designed microcyclones can achieve effective pollen removal with acceptable energy consumption, making them very suitable for different air pollutant analysis. The findings contribute to the advancement of microscale inertial separation devices for airborne allergen control.Keywords: separation, microdevices, cyclones, microcyclone, pollen
Keywords: separation, microdevices, cyclones, microcyclone, pollen